Critical Literacy in Indonesian ELT: A Multicultural Approach Based on Banks’ Dimensions of Education - Saputra, Heru; Dolendra Paudel (Kognisi: Jurnal Ilmu Keguruan, 2024)
In Indonesia’s diverse sociocultural landscape, English language teaching (ELT) is crucial in shaping students’ understanding of multicultural perspectives. However, ELT materials often lack cultural inclusivity and fail to encourage critical engagement with diverse narratives. This conceptual paper explores the integration of the Critical Literacy Approach in ELT to promote multicultural awareness among secondary school students. Using James A. Banks’ Dimensions of Multicultural Education as the analytical framework, this study examines how ELT materials and pedagogical strategies can foster students' ability to question biases, challenge stereotypes, and engage with diverse cultural perspectives. Through a critical review of Indonesian curriculum guidelines, ELT textbooks, and relevant literature, this study identifies how ELT content aligns with content integration, knowledge construction, prejudice reduction, equity pedagogy, and school empowerment—the five dimensions outlined by Banks. The analysis highlights key gaps in representation and suggests strategies for integrating critical literacy-based teaching practices, such as selecting diverse texts, encouraging dialogic discussions, and implementing equity-focused instructional methods. This paper contributes to ongoing discussions on multicultural education in ELT. It offers pedagogical insights for teachers, curriculum designers, and policymakers to create more inclusive and critically engaging English learning environments.